กระบวนการจัดทำรายละเอียดโครงการและการบริหารจัดการโครงการศูนย์ชุมชนแบบมีส่วนร่วมอย่างยั่งยืน: กรณีศึกษาศูนย์ชุมชนบึงพระรามเก้าและชุมชนบึงพระรามเก้าพัฒนา - ปรางโชสุก สุพรรณนานา (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The community center is the hub of the community. And as part of community development. Most community centers suffered from unsustainable. Due to the lack of participation of the community. And dependence on donations As a result, people are not used and cannot be managed. Research aims 1) study the education community. And participatory planning processes 2) to continue the process. analyze and conclude the preparation of the detailed project case studies 3) to analyze and planning, project management, community centers, 4) for a recommendation on the implementation of the next stage of the community center. And applied to other projects with similar factors. Using data collection, surveys, observations, inquiries, interviews, focus groups, brainstorming. And imagination using the map Write down and save the image as a tool for data collection. The results from the first phase to be publicized. Attitude to the importance of community centers and participate. And encourages the integration 1) Programming. It is used to collect data from people who are all involved. The researchers then used a critical essay with the community and orientation towards design guideline and feasibility study. The project area is 877 sq.m. Money for the construction of approximately 11,701,800 baht 2) Project Management. Funding for the construction of the community to work together to find yourself before a 15% share of the construction of a second before the interval. And divide the proceeds from a half after opening a money to repair the building. The conclusions of the study requested by the participating communities are likely to be used. And are planning to use the money donated in just in the building. And the community is managing the project to be profitable without relying on donations again. Community centers are likely to be sustainable, but with time restrictions on the research cannot measure the sustainability of the project was not full.